Calculating the Carbon Footprint from Different Classes of Air Travel - Bofinger, Heinrich (World Bank, Washington, DC, 2013)
This paper develops a new methodology for calculating the "carbon footprint" of air travel whereby emissions from travel in premium (business and first) classes depend heavily on the average class-specific occupied floor space. Unlike methods currently used for the purpose, the approach properly accounts for the fact that the relative number of passenger seats in economy and premium classes is endogenous in the longer term, so adding one additional premium trip crowds out more than one economy trip on any particular flight. It also shows how these differences in carbon attributable to different classes of travel in a carbon footprint calculation correspond to how carbon surcharges on different classes of travel would differ if carbon emissions from international aviation were taxed given a competitive aviation sector globally. The paper shows how this approach affects carbon footprint calculations by applying it to World Bank staff travel for calendar year 2009.